A Thousand No's - Corchin, D. J.; Dougherty, Dan (Naperville, Illinois : Sourcebooks Explore, 2020)
A little girl with a great idea is, at first, disheartened to hear "NO!", but with perseverance, collaboration, and imagination she finds a way to build something even greater.
Keywords: Adaptability (Psychology) -- Juvenile fiction; Persistence -- Juvenile fiction; Imagination -- Juvenile fiction; Cooperativeness -- Juvenile fiction; No (The English word) -- Juvenile fiction; Adaptability (Psychology) -- Fiction; Persistence -- Fiction; Imagination -- Fiction; Cooperativeness -- Fiction; No (The English word) -- Fiction